Studies on estimation of heterosis for striga resistance in maize test crosses in Mali - Sangare, S.; Menkir, A.; Ofori, K.; Gracen, V. (2019)
Heterosis for yield, secondary traits and Striga resistance was estimated in maize test crosses generated from fifteen inbred lines and three testers using line by tester analysis. Hybrids, testcrosses and parents were evaluated for two years at Agricultural Research Institute, Sotuba and Sanankoroba, to identify combinations expressing high hybrid vigor in Mali under Striga- infested and Striga-free conditions. Under Striga-free condition TZISTR106/TZISTR1230, TZISTR106/TZISTR1223 and TZISTR1033/ TZISTR1223 appeared as the best hybrids combinations with respect to grain yield, while combinations TZISTR1207/TZISTR1226, TZISTR106 /TZISTR112,TZISTR106 / TZISTR113 and TZISTR106/ TZISTR1028 showed positive mid parent heterosis for grain yield and negative mid parent heterosis for Striga related traits under Striga infestation. These hybrids are worthy for further utilization.